Centralized and decentralized provision of public goods - Janos Feidler; Klaas Staal (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2008)
We model the trade-off between centralized and decentralized decision making over the provision of local public goods. Centralized decisions are made in a legislature of locally elected representatives, and this creates a conflict of interest between citizens in different jurisdictions. The legislature can be self-interested or benevolent and this can result in either efficient, excessive or misallocative provision of public goods. Decisions are inuenced by spillover effects and differences in jurisdictionalsize. Furthermore, we look at the incentives for centralization.
urn:nbn:de:bvb:19-epub-13311-7
Keywords: H40; H70; P51; 330; decentralization; local public goods